نظام الريادة في الطاقة والتصميم البيئي(LEED) كمعيار تقييم لاستدامة التجمعات العمرانية حالة دراسية: مدينة غدامس القديمة نموذجا (Comprehensive Journal of Science, 2025)
The Zero Energy system, adopted by some countries in their current or future projects—whether in the design phase, under construction, or already existing—benefits the state by reducing operational costs and providing a more advanced sustainable environment. The Leadership in Energy and Environmental Design (LEED) certification is awarded to all types of projects, whether existing or new, that meet the specific requirements of this system. Most of these requirements can be found already implemented in many urban settlements of old cities, which have adapted to their environments and established the foundations of sustainable urban development in accordance with the principles of leadership in energy and environmental design.    The aim of this study is to highlight the evaluation criteria of the LEED system and assess their availability within the study area. The Old City of Ghadames was selected as a case study representing a sustainably developed urban fabric that continues to exist to this day with high environmental efficiency. The study seeks to determine the extent to which Ghadames meets the general criteria of the LEED system, and to draw lessons from it that can be applied in practice.   To achieve this goal, the researcher adopted both the descriptive and deductive methodologies, relying on multiple sources, illustrations, and analytical approaches.   The study reached specific conclusions showing that the urban fabric of Ghadames was designed and built according to a construction system whose main objective was to achieve the highest performance efficiency in terms of energy, human, and environmental aspects. The researcher included in this study numerous tables, diagrams, and photographs to be used as references for the development of sustainable urban communities with low energy and environmental costs.
Keywords: LEED System, Environmental Design, Urban Sustainability, Old Cities, Sustainable Urbanism, Energy.